Holiday Allowance for Domestic Workers - Salsabila Dhifah Putri; Manhem, Thipyada (Universitas Negeri Surabaya, 2024)
Domestic workers or domestic workers in Indonesia are considered to still exist and are still relevant. The role of domestic workers is considered important in the domestic life of domestic workers, where domestic workers replace the user's duties and obligations in taking care of the household. After domestic workers have completed their obligations, domestic workers are entitled to their rights. The rights of domestic workers are regulated in Article 7 of the Minister of Manpower Regulation Number 2 of 2015 concerning Protection of Domestic Workers. One of the rights contained in Article 7 of Minister of Manpower Regulation no. 2 of 2015, namely the right to receive a Holiday Allowance or THR. However, in Minister of Manpower Regulation no. 2 of 2015 does not yet explicitly regulate the amount of THR that should be received by domestic workers, so this can be a loophole for domestic workers to give nominal THR arbitrarily. The existence of this problem calls for legal protection which is one of the urgencies for domestic workers to be given their rights. There needs to be involvement from various elements to realize legal protection for domestic workers. The exact amount of THR allocated to domestic workers should be explained in detail, whether regulated in a written work agreement, regulations that specifically regulate THR for domestic workers and its implementation is supervised by the competent government. The research method used in this research is normative juridical by examining several literature and regulations related to this article. The approach methods used in this research are the statutory approach, conceptual approach and comparative approach. Comparison of regulations regarding the informal sector such as domestic workers in Indonesia itself should be more detailed, such as Hong Kong which really pays attention to the welfare of domestic workers or what are usually called domestic servants. Thus, the regulation of the amount of THR for domestic workers is considered to be unclear, which can lead to misinterpretation and this shows the existence of legal ambiguity.